Decarbonizing the Maritime Industry: A Collaborative Path Forward - Yudan Whulanza; Eny Kusrini; Muhamad Arif Budiyanto; Arnas; Yanuar (International Journal of Technology)
The maritime industry is embarking on an ambitious journey to decarbonize its operations, driven by collective frameworks and practical innovations that prioritize sustainability. The maritime industry's decarbonization journey is deeply influenced by international policies and regulatory frameworks. Key initiatives such as the IMO 2023 targets, the Energy Efficiency Existing Ship Index (EEXI), and the Carbon Intensity Indicator (CII) have created a strong mandate for reducing greenhouse gas emissions (IMO, 2023). Shipping industry leaders have emphasized the importance of collaboration, transparency, and data-driven strategies to reduce emissions and achieve environmental goals.